Perfectionism, Coping, and Underachievement in Gifted Adolescents: Avoidance vs. Approach Orientations - Emily Mofield; Megan Parker Peters; Sumita Chakraborti-Ghosh (MDPI AG, 2016)
Perfectionism can influence how one approaches challenges and deals with setbacks, and, consequently, can inhibit or facilitate achievement. The present study (1) explored the relationship between Frost's six dimensions of perfectionism and five types of coping strategies; (2) examined how dimensions of perfectionism predict coping in response to academic stress; and (3) investigated differences between gifted underachievers and other gifted students on perfectionism and coping among 130 American gifted students in grades 6-8. Results of stepwise regression models revealed approach coping was predicted by adaptive perfectionism (Positive Strivings-notably Organization), whereas avoidance coping (Internalizing, Externalizing, and Distancing) was predicted by various combined models. Gifted underachievers displayed lower Positive Strivings perfectionism scores and lower positive coping when compared to achievers. This information is helpful when considering ways to guide gifted students to high levels of academic achievement while utilizing adaptive approaches.